Decades of reconstruction postwar societies, state-building, and international relations from the Seven Years' War to the Cold War - Planert, Ute 1964-; Retallack, James N. 1955- (Publications of the German Historical Institute, 2017)
International scholars review decades of postwar reconstruction in international comparison from the eighteenth to the twentieth century, demonstrating how foreign domestic policy cannot be separated